ADVANCED IMAGING AND MOLECULAR TECHNOLOGIES IN FORENSIC MEDICINE: NEW DIRECTIONS AND PRACTICAL APPLICATIONS. - Hikmatullaev Ruhulla Zabihullaevich; Ganiyeva Nilufar Xamroevna (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: Recent developments in imaging and molecular technologies have significantly reshaped the landscape of forensic medicine. Conventional autopsy, although considered the gold standard for determining cause of death, presents limitations such as invasiveness, time consumption, and cultural or legal restrictions. Modern imaging techniques, including post-mortem computed tomography (PMCT), magnetic resonance imaging (MRI), and three-dimensional reconstruction—collectively referred to as virtual autopsy—offer a non-invasive alternative for comprehensive visualization of internal structures. These methods allow accurate detection of fractures, hemorrhages, air embolism, and pathological changes that may not be evident during traditional dissection.